1982
DOI: 10.1083/jcb.94.2.400
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of proadipocyte growth arrest and differentiation. II. A cell cycle model for the physiological control of cell proliferation.

Abstract: Experimental evidence is presented that supports a cell cycle model showing that there are five distinct biological processes involved in proadipocyte differentiation. These include: (a) growth arrest at a distinct state in the G1 phase of the cell cycle; (b) nonterminal differentiation; (c) terminal differentiation; (d) loss of the differentiated phenotype; and (e) reinitiation of cell proliferation. Each of these events is shown to be regulated by specific human plasma components or other physiological facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 14 publications
4
49
0
Order By: Relevance
“…Furthermore, several genes that have been suggested to be involved in the control of the proliferative state of cells were downregulated, such as metastatic cell protein, drm (downregulated in mos-transformed cells), a 21-kDa peptide that is under translational control in tumor cells, hydrophobic nucleolar protein (HNP36), a large subunit of transforming growth factor (TGF)-␤ masking protein, gas 1 (growth-arrest specific gene 1), and a polypeptide having biological activity relating to proliferation and propagation of cells. This is, in most cases, well in agreement with previous findings indicating that differentiation of 3T3-L1 cells involves growth arrest (35) and that ligand-activated PPAR-␥ is sufficient to induce growth arrest (36). However, the downregulation of the large subunit of TGF-␤ masking protein, which neutralizes the activity of TGF-␤1, is surprising because TGF-␤1 has previously been shown to inhibit adipocyte differentiation (37).…”
Section: Resultssupporting
confidence: 79%
“…Furthermore, several genes that have been suggested to be involved in the control of the proliferative state of cells were downregulated, such as metastatic cell protein, drm (downregulated in mos-transformed cells), a 21-kDa peptide that is under translational control in tumor cells, hydrophobic nucleolar protein (HNP36), a large subunit of transforming growth factor (TGF)-␤ masking protein, gas 1 (growth-arrest specific gene 1), and a polypeptide having biological activity relating to proliferation and propagation of cells. This is, in most cases, well in agreement with previous findings indicating that differentiation of 3T3-L1 cells involves growth arrest (35) and that ligand-activated PPAR-␥ is sufficient to induce growth arrest (36). However, the downregulation of the large subunit of TGF-␤ masking protein, which neutralizes the activity of TGF-␤1, is surprising because TGF-␤1 has previously been shown to inhibit adipocyte differentiation (37).…”
Section: Resultssupporting
confidence: 79%
“…The myc-sensitive point in G1 is reminiscent of the GD state that has been described for BALB/c 3T3 proadipocytes by Scott and co-workers (29,30,38). In this system, the growth arrest that immediately precedes terminal differentiation is postulated to occur at a point earlier in G1 than that seen with either serum deprivation or nutrient starvation.…”
Section: Discussionmentioning
confidence: 85%
“…When cells were treated with dihydroteleocidin B after the induction stage, in which commitment had already taken place, a certain number of adipocytes was observed, although insulin no longer enhanced differentiation. Recently Scott et al (15) and Wille and Scott (21) suggested the existence of several substages in the adipocyte differentiation process under serum-containing conditions. They postulated a mechanism of re-initiation of the cell cycle.…”
Section: Discussionmentioning
confidence: 99%